The Influence of Using Social Media Instagram @Fanirahm to Fulfill the Information Needs of Beauty Products for Generation Z in Bandung City - Nurmalia Dewi Putri; Dindin Dimyati (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The existence of technological developments in this digital era brings people into easy life with activities without any limitations of space and time. Social media has now become a new medium for people to communicate, making the use of social media becomes part of people's lives. It can be seen by the data presenting the large number of internet and social media users. Through this high usage, beauty content creators have emerged, one of whom is Fani Rahmawati. She is a source of information about beauty products. This research aims to determine the magnitude of the influence of the use of social media Instagram @fanirahm on fulfilling the information needs for beauty products among Generation Z in Bandung City. The indicators tested in the research employed social media use variables with the dimensions of context, communication, collaboration, connection and information need variables with the dimensions current need approach, daily need approach, exhaustive need approach, and catching-up need approach. The research method used quantitative with descriptive research type involving the Generation Z population in Bandung City. Sampling was carried out using a random sampling technique, with a sample size of 400 people through distributing questionnaires. The research results indicate that the use of social media Instagram @fanirahm has a positive and significant influence of 86,3% on fulfilling the information needs of Generation Z in Bandung City. For future researchers, they are able to conduct research on the same topic but using different research methods.